The Forgotten Infection Cases: Leprosy Disease Oral Manifestations and Its Problem - Nurfianti, Nurfianti (Indonesian Dental Association, 2024)
Background: Leprosy, an infectious disease caused by Mycobacterium leprae, predominantly affects the skin, peripheral nerves, and mucous membranes. Although highly contagious, most people are naturally resistant. Indonesia ranks third globally in leprosy cases, and the disease continues to pose a significant public health challenge. This report aims to highlight the oral manifestations of leprosy in order to aid in early detection and treatment, which are essential to prevent disability and stigma. Case(s): Five patients diagnosed with borderline lepromatous or lepromatous leprosy were examined. Their oral manifestations included gingivitis, periodontitis, ulceration, desquamation, anesthesia, and hypopigmented lesions. Some patients exhibited poor oral hygiene, which exacerbated their symptoms. Each patient was undergoing multidrug therapy with rifampicin, dapsone, and clofazimine, along with additional medications based on individual systemic conditions. Discussion: The oral manifestations observed in these cases, such as ulceration and epithelial desquamation, are characteristic of advanced leprosy. Early diagnosis through recognition of oral symptoms is critical in preventing irreversible physical and social consequences. Dentists can play a key role in identifying leprosy, particularly when examining patients in endemic regions. Conclusion: Oral manifestations of leprosy provide an important diagnostic tool for early detection, potentially preventing severe complications, including physical disability and the associated socio-economic challenges. Dentists should be aware of these symptoms to help improve treatment outcomes and patient quality of life.